Language in prehistory - Barnard, Alan (Approaches to the evolution of language, 2016)
"For ninety per cent of our history, humans have lived as 'hunters and gatherers', and for most of this time, as talking individuals. No direct evidence for the origin and evolution of language exists; we do not even know if early humans had language, either spoken or signed. Taking an anthropological perspective, Alan Barnard acknowledges this difficulty and argues that we can nevertheless infer a great deal about our linguistic past from what is around us in the present. Hunter-gatherers still inhabit much of the world, and in sufficient number to enable us to study the ways in which they speak, the many languages they use, and what they use them for. Barnard investigates the lives of hunter-gatherers by understanding them in their own terms, to create a book which will be welcomed by all those interested in the evolution of language"--